Students' 21st-Century Economic Competencies in The Digital Age : Exploring The Interplay Between Artificial Intelligence, Augmented Reality, and Learning Engagement - Winokan, Amsje Norma; Arsana, I Kadek Satria; Dame, Joubert Mandri; Dolonseda, Herman Philips (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to analyze the effect of Artificial Intelligence (AI) and Augmented Reality (AR) on high school students' 21st century economic competencies with learning engagement as a mediating variable. Using a quantitative approach with an explanatory survey design, the study involved 358 public high school students in Bitung City selected through proportional stratified random sampling. Data were collected using a 5-point Likert scale questionnaire and analyzed by Structural Equation Modeling based on Partial Least Squares (SEM-PLS) through SmartPLS 4. Results showed that AI (β = 0.364, p < 0.001) and AR (β = 0.498, p < 0.001) significantly influenced learning engagement, which in turn influenced 21st century economic competence (β = 0.654, p < 0.001). Learning engagement partially mediated the AI-competence (β = 0.238) and AR-competence (β = 0.326) relationships. The model explained 51.5% of learning engagement variance and 42.8% of 21st century economic competence variance. The findings resulted in a dual-technology competency development framework that integrates dual technology capabilities through direct and mediated pathways. Research implications emphasize the importance of differentiated learning technology implementation and teacher training that is responsive to the needs of AI-AR integration. The synergistic integration of AI and AR is proven to be a transformative catalyst in shaping students' competencies in the digital era.